An Analysis of Student Perspectives on STEM through Science Learning in Bandung City, Indonesia - Ida Kaniawati, SrikandiRayuni, Irma RahmaSuwarma, Harun Imansyah, EndiSuhendi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this 21st century, STEM (Science, Technology, Engineering, and Mathematics) - based Science learning has been widely applied in schools. To produce better STEM-based science learning, information is needed about students' perspectives on STEM. The required information includes students' perspectives on interests, careers, and STEM content. This research was conducted to obtain information about interests, careers, and STEM content. The sample used was grade IX (nine) students in one State Junior High School in Bandung. The method of the study employed a survey method using a five-scale Likert questionnaire and was analysed using descriptive statistics. It categorized students' perspectives on STEM learning in five categories namely very positive, positive, less positive, negative, and very negative categories. The results showed that most of the students' perspectives on the interests of using STEM were in the positive category with a percentage of 64%. Most of the students' perspectives on the STEM careers were in the positive category with a percentage of 80%. And students' perspectives on the content of STEM were mostly in the positive category with a percentage of 62%.